2022
DOI: 10.3390/md20100606
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Inflammatory Activities of Fucoidans from Five Species of Brown Seaweeds

Abstract: This study aimed to compare the anti-inflammatory effects of fucoidans from brown seaweeds (Saccharina japonica (SJ), Fucus vesiculosus (FV), Fucus distichus (FD), Fucus serratus (FS), and Ascophyllum nodosum (AN)), and determine the relationship between composition and biological activity. The anti-inflammatory activity was tested in vitro. It is believed that inflammation could be triggered by free radicals. Fucoidans from F. vesiculosus (FV1 and FV3) showed the strongest 1,1-diphenyl-2-picrylhydrazyl (DPPH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…Following Obluchinskaya et al with some modifications [ 12 ], 10 mg of each fucoidan sample were hydrolyzed in 0.5 mL 2 M trifluoracetic acid at 100 °C for 3 h. Following that, the solutions were cooled in ice bath and then the pH was adjusted at 7.0 by 2 M NaOH. The analyzed samples were hydrolyzed fucoidans in addition to several neutral sugar monomers as glucose, fucose, galactose, mannose, and rhamnose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Obluchinskaya et al with some modifications [ 12 ], 10 mg of each fucoidan sample were hydrolyzed in 0.5 mL 2 M trifluoracetic acid at 100 °C for 3 h. Following that, the solutions were cooled in ice bath and then the pH was adjusted at 7.0 by 2 M NaOH. The analyzed samples were hydrolyzed fucoidans in addition to several neutral sugar monomers as glucose, fucose, galactose, mannose, and rhamnose.…”
Section: Methodsmentioning
confidence: 99%
“…Fucoidans have shown potential bioactivities, including antioxidant, anti-coagulant, anti-tumor, anti-inflammatory, and management of metabolic diseases and kidney dysfunction [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] with furtherly formulated in pharmaceutical preparations as an essential step for clinical investigations and commercial marketing [ 20 ]. However, the recent studies found that the antioxidant activity is correlated potentially with the phenolic contents in crude fucoidan extracts [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the relatively high molecular weight, negatively charged sulfate groups, and hydrophilicity, fucoidans generally have a low skin permeation coefficient. It was also found that the anti-inflammatory effect of fucoidan, especially that based on the inhibition of protein denaturation, is dependent on the fucose and sulfate content of the extract obtained from five different brown seaweed species, which are Saccharina japonica, F. vesiculosus, Fucus distichus, Fucus serratus, and Ascophyllum nodosum [ 74 ].…”
Section: Pharmaceutical Dosage Forms Of Fucoidan and Their Different ...mentioning
confidence: 99%
“…Fucoidan is essentially composed of L-fucose and sulfate ester groups, presenting different biological activities dependent on its source and its molecular weight, type of sugar content, sulfation degree, molecular structure, harvesting, and extraction conditions [ 16 ]. The most reported properties are antitumor [ 17 , 18 , 19 , 20 , 21 ], antiviral [ 22 , 23 ], anti-inflammatory [ 24 , 25 , 26 , 27 , 28 , 29 ], and anticoagulant [ 26 , 30 , 31 , 32 , 33 ], but also skin management potential [ 34 , 35 , 36 , 37 ]. Pozharitskaya and colleagues evidenced the cutaneous application of fucoidan with pharmacokinetic studies in rats, which indicated fucoidan’s ability to cross the skin barrier and accumulate in the striated muscles [ 38 ].…”
Section: Introductionmentioning
confidence: 99%